Resilient Connectivity: Leveraging Pocket Switched Networks for Post-Disaster Communication - Sarkar, Ratna R.; Chakrabarty, Amitabha; Rahman, Mohammad Zahidur (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The Pocket Switched Network (PSN) serves as a communication paradigm suitable for scenarios where the conventional network infrastructure is either damaged or intermittently available. Positioned within the domain of Delay-Tolerant Networks (DTN), PSN operates without a fixed infrastructure and leverages human mobility patterns to determine optimal routing. Because of the damaged communication infrastructure, this communication concept finds practical application in areas affected by natural catastrophes. In this research, a thorough analysis of several routing algorithms used in Pocket Switched Networks (PSN) is conducted. It also presents a paradigm based on PSN concepts that is intended to support resilient communication in post-disaster situations.